Optimasi Pemantauan Kualitas Air Baku Dengan Metode Arima dan Teknologi IOT pada Bak Sedimentasi IPA III - Sari, Asri Fornika; Panjaitan, Seno D; Sanjaya, Bomo W (Jurnal Teknologi Lingkungan Lahan Basah, 2024)
The provision of clean water is an important necessity for society, with water utilities playing an important role in ensuring good water quality. Water quality directly affects health, therefore, monitoring it is very important. This research designs an IoT-based raw water quality monitoring tool in the Sedimentation Basin at PERUMDA Air Minum Tirta Khatulistiwa Pontianak using Raspberry Pi Pico W. This tool allows real-time monitoring and prediction of water pH, temperature, and turbidity for the next seven days using the ARIMA method. The focus on IoT integration aims to improve monitoring efficiency and response to changing water conditions, overcoming the constraints of manual monitoring. The results showed the MAPE of the monitoring tool was 2.30% and the MAPE of the prediction was 6.41%. This signifies the reliability of the tool in accurately measuring and predicting raw water quality.